Pragmatic Functions of Speech Acts in Arabic Language Learning: A Case Study from Madura - Mustahar Ali Wardana; Segaf Baharun (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Despite growing recognition of communicative competence in second language acquisition, Arabic instruction in Islamic boarding schools (pesantren) often remains focused on grammar, overlooking pragmatic competence. This gap limits students’ ability to use Arabic appropriately in real-life interactions, particularly in directive and assertive forms of speech. This study addresses that gap by exploring how students at Darul Lughah Waddirosatil Islamiyah in Madura perform Arabic speech acts within an immersive environment. The research aims to analyze the variation and functions of directive and assertive speech acts and how these contribute to effective communication and pedagogy. Using a qualitative case study design, data were collected through observations, interviews, and document analysis involving 30 advanced-level students. Results show that students strategically adjust their speech based on roles, social hierarchy, and interactional context often using indirect forms and politeness markers. These patterns emerged naturally through immersion rather than formal instruction. The findings highlight the importance of integrating pragmatics into Arabic curricula, emphasizing culturally and contextually appropriate communication. Such integration promotes not only language fluency but also socio-religious sensitivity, aligning Arabic education with both communicative and ethical goals.